Analysis and experimental testing of a self-centering controlled rocking wall with buckling-restrained braces at base. (15th October 2022) - Jiang, Qing; Wang, Hanqin; Feng, Yulong; Chong, Xun; Huang, Junqi; Wang, Shaoying; Zhou, Yating
Highlights: This study proposed a SC-CRWBB by introduced BRBs at corner and UPTs at center to CRW. The seismic performance of SC-CRWBB was studied through the quasi-static tests. The influence of UPTs initial stress and BRB area on residual drift was analyzed. The hysteretic curve and the required UPTs initial stress were theoretically deduced. Abstract: A new self-centering controlled rocking wall (CRW) with buckling-restrained braces (BRBs) at the base (SC-CRWBB) is proposed to improve the energy dissipation and self-centering capacities of CRWs. The SC-CRWBB was established by adding unbonded posttensioned tendons (UPTs) at the center and BRBs at two corners of a CRW. The quasi-static test results demonstrated that the proposed SC-CRWBB achieved a satisfactory seismic performance. Structural damage was concentrated in the BRBs, while a few cracks occurred in the surface between the CRW and mortar layer and between the BRBs and CRW. Then, a finite element model (FEM) of the test specimen was created in ABAQUS software to study the influence of the initial stress of the UPTs and sectional area of the BRB core plate on the residual deformation and lateral carrying capacity of the SC-CRWBB. Finally, an analytical method for the investigation of SC-CRWBBs was validated against the test and FE analysis results.